Portfolio Selection in BSE: Expected Return and Risk Analysis through Markowitz Theorem - Rajasekaran, N. (Indian Journal of Finance, 2012)
Market capitalization in India remains to be considerably low and dwindling consistently to the level of 0.8 per cent of the GDP. Though a financial sector is expected to grow as the economy grows, the growth of the financial sector raises skepticism on the robustness of the growth of the economy. It also envisages the opportunities for the growth in the financial sector. The study delves into the risk and return of different portfolios in relation to benchmark indices in the BSE. The Markowitz’s theorem and analysis are used to understand the risk and returns. The results indicate that there is high scope for growth in returns and the risk prevalent in the market is an increasingly systematic risk. This manifests the need for financial stability in the economy and proper systems in place for financial regulation to overcome the systematic risk. This would prepare the platform for the efficient market.